Isolation, characterization and modification of citrus pectins - MARIA KRATCHANOVA; IRINA YANAKIEVA; MANOL OGNYANOV; YORDAN GEORGIEV; VESELIN KUSSOVSKI (Journal of BioScience and Biotechnology, 2012)
Orange and lemon peels were used for obtaining pectic polysaccharides. Citrus peels were previously treated with 96% ethanol, and the obtained alcohol-insoluble solids (AIS) were subjected to a sequential extraction with hot distilled water and hot 0.5% HCl. Water- and acid-extracted orange (WEOP and AEOP) and lemon (WELP and AELP) pectins were obtained. Acid extraction gave higher yields of pectin than water extraction and lemon peels were richer in pectin. Comparative investigations were carried out with chromatographically purified commercial citrus pectin (CPCP). Chemical and physicochemical characterization of all pectins was accomplished. It was found that pectins were similar in anhydrouronic acid content (AUАC, 69-81%), but differed in their degree of methylesterification (DM, 55-81%). Generally water-extracted pectins were with higher DM. Both orange pectins were with higher DM and degree of acetylation (DA, 2%), in comparison with the corresponding lemon pectins. Water-extracted pectins were with higher degree of feruloylation (DF, 0.12-0.34%). To our knowledge this is the first report on the estimation of ester-linked ferulic acid in orange and lemon peel pectins. Pectic polysaccharides differed in molecular weight and homogeneity. WELP was with the highest molecular weight and homogeneity. The pectins contained D-galacturonic and D-glucuronic acids, L-arabinose, D-galactose, L-fucose, L-rhamnose and D-xylose. All investigated pectins showed immunostimulating activity by complement activation in the classical pathway at 1.25 and 2.5 mg/mL. Pectic polysaccharides were modified with endopolygalacturonase. Enzyme-modified CPCP and WEOP had higher anti-complementary activity than the corresponding initial pectins.